Regeneration and conservation of the communitary forest, the case of Chichila, Guerrero - Valencia Negrete, Mauricio; Castillo Santiago, Miguel Angel; Bello Baltazar, Eduardo; Vásquez Sánchez, Miguel Ángel (Instituto de Ecología, A.C., 2022)
Although the causes of land use change have been studied globally, there are few detailed studies on the local scale. In this paper, we studied land cover and land use changes in an agrarian community in Guerrero, Mexico, over 24 years period. Satellite images and orthophotos were photo interpreted to produce high-resolution land cover and land use maps for 1995, 2009 and 2019. In addition, interviews were conducted with key stakeholders and, production statistics were collected and analyzed to identify the causes of land use change. Our results show that from 1995 to 2009, forest cover increased by 259 ha (5.3%), and agriculture areas decreased by 145 ha (3%). In the last stage (2009-2019), forest cover increased by 56 ha (1.2%), and agriculture decreased by 59 ha (1.2%). The recovery of forest cover was related to a couple of concomitant factors, such as the abandonment of agricultural land due to migration and the strengthening of the access rules to forest resources, the latter motivated mainly by the benefits obtained from the provision of hydrological services of the community forests.